2010
DOI: 10.1074/jbc.m110.100545
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-dependent Transcription of the NEL-like 2 (NELL2) Gene and Its Role in Protection from Cell Death

Abstract: NELL2 (neural tissue-specific epidermal growth factor-like repeat domain-containing protein) is a secreted glycoprotein that is predominantly expressed in neural tissues. We reported previously that NELL2 mRNA abundance in brain is increased by estrogen (E2) treatment and that NELL2 is involved in the E2-dependent organization of a sexually dimorphic nucleus in the preoptic area. In this study we cloned the mouse NELL2 promoter and found it to contain two half-E2 response elements. Electrophoretic mobility shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 50 publications
8
42
0
Order By: Relevance
“…Western blot analysis revealed that NELL2 expression was significantly increased by E2 in the POA of OVX female rats (Figs. 2A and 2B), which concurs with our previous finding of positive E2 action on NELL2 expression (Choi et al, 2010). Real-time PCR analysis also revealed that E2 increased KiSS1 mRNA levels in the POA (Fig.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Western blot analysis revealed that NELL2 expression was significantly increased by E2 in the POA of OVX female rats (Figs. 2A and 2B), which concurs with our previous finding of positive E2 action on NELL2 expression (Choi et al, 2010). Real-time PCR analysis also revealed that E2 increased KiSS1 mRNA levels in the POA (Fig.…”
Section: Resultssupporting
confidence: 81%
“…This finding is consistent with the results of our previous studies showing that E2 activates NELL2 transcription (Choi et al, 2010) and that NELL2 is expressed in the ERα expressing hypothalamic cells (Choi et al, 2010;Jeong et al, 2008a).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations